Deformation monitoring by using the combination of geotechnical and geodetic observable - Setan, Halim; Amri, Yul (2004)
Large structures such as dams undergo deformation. Deformation monitoring is required to ensure the dams are secured during its operational life. Among the various scheme of monitoring, the deformation monitoring via geodetic method can be applied to obtain the status of displacement vector of the surface object points under investigation. Geotechnical observables are complementary to the geodetic network observables for the deformation modeling purpose. Geodetic network provides the absolute displacement vector of the object points on the surfaces of the body under investigation while the geotechnical measurement provides the relative displacement inside the body. This paper describes the combination scheme of the geodetic and geotechnical observables to determine the deformation model. The whole scheme of the computer program to handle the deformation analysis is also described. The preliminary results of some modules of the program are presented, followed by some important recommendations.